Neuroprotective and Neurorescue Mode of Action of Bacopa monnieri (L.) Wettst in 1-Methyl-4-phenyl-1,2,3,6-tetrahydropyridine-Induced Parkinson’s Disease: An In Silico and In Vivo Study - Singh, Babita; Pandey, Shivani; Rumman, Mohammad; Kumar, Shashank; Kushwaha, Prem Prakash; Verma, Rajesh; Mahdi, Abbas Ali (Frontiers in Pharmacology, 2021)
Ethnopharmacological relevance: Parkinson's disease (PD) is characterized by progressive death of dopaminergic neurons. The presently used medicines only tackle the symptoms of PD, but none makes a dent on the processes that underpin the disease's development. Herbal medicines have attracted considerable attention in recent years. Bacopa monnieri (L.) Wettst (Brahmi) has been used in Indian Ayurvedic medicine to enhance memory and intelligence. Herein, we assessed the neruo-protective role of Bacopa monnieri (L.) Wettst on Parkinson’s disease. Aim of the study: Bacopa monnieri (L.) Wettst, a medicinal herb, is widely used as a brain tonic. We investigated the neuroprotective and neurorescue properties of Bacopa monnieri (L.) Wettst extract (BME) in 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP)-induced mice model of PD. Materials and Methods: Mice model of MPTP-induced PD is used in the study. In the neuroprotective (BME+MPTP) and neurorescue (MPTP+BME) experiments, the animals were administered 40 mg/kg body weight BME orally before and after MPTP administration, respectively. Effect of BME treatment was evaluated by accessing neurobehavioral parameters, and levels dopamine, glutathione, lipid peroxide, and nitrites. In-silico study was performed using Auto Dock Tools 1.5.6 (ADT). Results: A significant recovery in behavioral parameters, dopamine level, glutathione level, lipid peroxides, and nitrite level was observed in BME-treated mice. Treatment with BME before or after MPTP administration has a protective effect on dopaminergic neurons, as evidenced by a significant decrease in GFAP immunostaining and expression of inducible nitric oxide synthase (iNOS) in the substantia nigra region; however, the degree of improvement was more prominent in mice receiving BME treatment before MPTP administration. Moreover, in silico study revealed that the constituents of BM, including bacosides, bacopasides, and bacosaponins can inactivate the enzyme monoamine oxidase B, thus, preventing the breakdown of MPTP to MPP+. Conclusion: Our results showed that BME exerts both neuroprotective and neurorescue effects against MPTP-induced degeneration of the nigrostriatal dopaminergic neurons. Moreover, BME may slow down the disease progression and delay the onset of neurodegeneration in PD.